PROFIL PEMECAHAN MASALAH SISWA KELAS VII-D PADA MATERI SEGITIGA SIKU-SIKU DI SMPN 1 PAMONA UTARA DITINJAU DARI PERBEDAAN GENDER: Profile Of Problem Solving Of Class VII-D Students On Right Triangle Material At SMPN 1 Pamona Utara Viewed Through Gender Differences - Borosi, Miranda Adhitya; Pathuddin; Paloloang, Baharuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
This study aims to have a describe the mathematical problem solving profile of class VII-D students at SMPN 1 Pamona Utara on right triangle material in terms of gender differences. The subjects in this research were class VII-D students at SMPN 1 North Pamona, consisting of 1 boy and 1 girl with high mathematical abilities. The results of this research show that (1) The male student subject's problem solving profile can understand the problem by determining what is asked and known. However, SL did not write down the complete information obtained on the answer sheet. SL can plan problem solving by determining appropriate problem solving strategies. At the implementation stage, the SL problem solving plan can be implemented according to the determined strategy. At the re-checking stage, SL did not re-check the explanation. SL can draw conclusions from the results of problem solving but does not write them on the answer sheet. (2) Female students' problem solving profile can understand the problem by determining what is asked and known and writing it on the answer sheet. SP can plan problem solving by determining appropriate problem solving strategies. At the implementation stage, the SP problem solving plan can be implemented according to the determined strategy. At the re-checking stage, SP did not re-check the explanation. SP can draw conclusions from the results of problem solving but does not write them on the answer sheet.